A Clinical Trial of Patient Reported Alterations in Pain and Opioid Intake Following Paracetamol and Magnesium Sulfate after Orthognathic Surgery - Rizwan Qureshi, Hafza Mahnoor Kaleem, Waleed Javaid Toosy, Muhammad Imtiaz, Muhammad Farooq (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Objectives: Paracetamol and magnesium sulphate may aid in pain management, which is crucial to examine in view of the potential detrimental effects of taking opioids increased doses postoperatively for pain management.This study investigated the impact of paracetamol and magnesium sulphate on the amount of pain experienced after orthognathic surgery, as well as the amount of opioids needed. Place of Study: Avicenna Medical College Lahore Study Duration: January 2021 to December 2021 Materials and Methods: Patients who were due to undergo bimaxillary orthognathic surgery were separated into two groups, each containing 20 individuals, for the purpose of this randomized, double-masked clinical experiment. Patients in group 1 received an intravenous infusion of 1 gram of acetaminophen (paracetamol) within 20 minutes, while patients in group 2 received an intravenous infusion of magnesium sulphate at a rate of 50 milligrams per kilogram one hour before the surgery was completed. Before the patients were permitted to leave the recovery area, they were given a visual analogue scale and asked to rate their level of discomfort on it. This proceeded at the same four-hour intervals for the next twelve hours (VAS). A dose of 30 milligrams of pethidine was delivered to anyone with a pain score of five or higher at any time. Results: In addition to the Chi-square test, the t-test, and the Mann-Whitney U test, the data were analyzed using the generalized estimating equation (GEE).(P > 0.05) There was no statistically significant difference in the amount of pain reported by either group during recovery or after 4 and 8 hours. This was true at all three time intervals. At the 12-hour point, the pain score of the magnesium sulphate group was considerably lower than that of the other groups (P = 0.008). It was concluded that there was no discernible change in the required amount of pethidine (P>0.05). Conclusion: It was shown that magnesium sulphate was marginally more effective than paracetamol at reducing postoperative pain and the need for opioids. Both magnesium sulphate and paracetamol were effective in alleviating postoperative pain and minimizing the need for opioids. Keywords: Acetaminophen; Magnesium Sulfate; Analgesics, Opioid; Orthognathic Surgery; Pain